Balancing globalization and linguistic heritage involves preserving mother tongues through inclusive education that values cultural identity and language diversity - Sumartana, I Made; Rouf, Md. Abdur; Hudiananingsih, Putu Dyah (Journal of Language, Literature, Social and Cultural Studies, 2025)
In the era of educational globalization, the preservation of mother tongues has become a critical concern for educators, linguists, and policymakers. The dominance of global languages such as English in educational curricula and academic discourse often leads to the marginalization of indigenous and minority languages. This study aims to explore the challenges and opportunities associated with preserving mother tongues within globalized educational frameworks. It seeks to highlight the implications of language loss on cultural identity, intergenerational communication, and linguistic diversity. The research employs a qualitative descriptive method, utilizing literature review, case studies, and interviews with educators and language activists from multilingual communities. The analysis reveals that while globalization facilitates access to international knowledge and collaboration, it also pressures educational institutions to prioritize global languages, often at the expense of local linguistic heritage. Case studies from regions such as Southeast Asia, Sub-Saharan Africa, and Latin America demonstrate how communities are attempting to integrate mother tongues into formal education through bilingual or multilingual education models. Interviews indicate that successful preservation efforts often depend on community involvement, governmental support, and curriculum integration that values both global and local knowledge systems. The study concludes that preserving mother tongues in education is not only a matter of linguistic justice but also of cultural sustainability. It emphasizes the need for inclusive language policies that balance global communication demands with the rights of communities to maintain their linguistic identities. Educational institutions must embrace multilingualism as an asset rather than a hindrance to progress. Further research is recommended to develop scalable models of mother-tongue-based multilingual education that can be adapted across diverse educational settings.